Classroom e-Science: Exposing the Work to Make it Work - Smith, Hilary; Underwood, Joshua; Fitzpatrick, Geraldine; Luckin, Rosemary (Educational technology & society, 2009)
Engaging students in science learning can be challenging, and incorporating new forms of technology into science has been shown to provide creative learning experiences. However most technology enhanced learning and e-Science experiences to date have been designed and run by researchers. There is significant challenge in moving these experiences into the hands of teachers to become an everyday part of learning. One step forward is to understand better the work involved in making these learning experiences work. We present a retrospective analysis of two educational e-Science research projects, each involving access to and analysis of scientific data from remote and handheld sensors; collaboration; and reviewing shared data using advanced software tools. We identify key categories of work from the effort, resources and issues entailed in setting-up and running these experiences. We propose these categories can be used: to help plan other technology enhanced learning experiences, to be further tested and evolved in future research, and as a basis for an overall experience framework to capture the process- and context-related aspects in which these tasks are embedded. Ultimately, the goal is to develop tools and resources that will support categories of significant work, enabling full classroom integration of e-Science learning experiences.